2022
DOI: 10.1186/s13256-022-03524-2
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent squamous cell carcinoma and a novel mutation in a patient with xeroderma pigmentosum: a case report

Abstract: Background Xeroderma pigmentosum is an extremely serious genetic disorder defined by sensitivity to sunlight, resulting in sunburn and pigment changes. If patients are not completely protected from ultraviolet radiation, xeroderma pigmentosum is characterized by a greatly increased risk of sunlight-induced cutaneous neoplasms. There is no standard therapy for skin cancer of xeroderma pigmentosum. However, immune checkpoint inhibitors were reported to increase response rates and improve outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…Eighteen months later, he developed a recurrence of cSCC on the neck and restarted ICI treatment. At the time of publication, the patient showed remission of the recurrent cSCC (28). Another XP patient showed remission of a metastatic melanoma treated with ipilimumab and regression of an unresectable maxillary sinus SCC treated with pembrolizumab.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Eighteen months later, he developed a recurrence of cSCC on the neck and restarted ICI treatment. At the time of publication, the patient showed remission of the recurrent cSCC (28). Another XP patient showed remission of a metastatic melanoma treated with ipilimumab and regression of an unresectable maxillary sinus SCC treated with pembrolizumab.…”
Section: Resultsmentioning
confidence: 97%
“…Before ICI treatment, seven patients with metastatic melanoma (two patients), sarcomatoid carcinoma (one patient (23)), metastatic cutaneous SCC (cSCC) (two patients (27,28))), and unresectable or metastatic angiosarcoma (two patients (22,32) did not respond to treatment with cytokines, chemotherapy, radiotherapy, targeted antibody therapy (Supplementary Tables S1-S3). In contrast, all 22 patients in the study showed regression or remission of the target cancer in response to ICI (treatment duration ranged from 2 to 60 months) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation